2017
DOI: 10.1002/anie.201702401
|View full text |Cite
|
Sign up to set email alerts
|

A Structurally Characterized Fluoroalkyne

Abstract: The facile synthesis of a stable and isolable compound with a fluoroalkynyl group, M-C≡CF, is reported. Reaction of [Ru(C≡CH)(η -C Me )(dppe)] with an electrophilic fluorinating agent (NFSI) results in the formation of the fluorovinylidene complex [Ru(=C=CHF)(η -C Me )(dppe)][N(SO Ph) ]. Subsequent deprotonation with LiN(SiMe ) affords the fluoroalkynyl complex [Ru(C≡CF)(η -C Me )(dppe)]. In marked contrast to the rare and highly reactive examples of fluoroalkynes that have been reported previously, this compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…These characteristics were also found with 5b , as shown in Figure S8. Interestingly, a dichromatic nature has been reported for the related fluorovinylidene complex [Cp*Ru­(CCHF)­(dppe)]­[PF 6 ], which was isolated as green crystals without solvation and orange crystals with CH 2 Cl 2 solvate, although the reason was not clarified. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics were also found with 5b , as shown in Figure S8. Interestingly, a dichromatic nature has been reported for the related fluorovinylidene complex [Cp*Ru­(CCHF)­(dppe)]­[PF 6 ], which was isolated as green crystals without solvation and orange crystals with CH 2 Cl 2 solvate, although the reason was not clarified. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Interestingly, a dichromatic nature has been reported for the related fluorovinylidene complex [Cp*Ru(CCHF)(dppe)][PF 6 ], which was isolated as green crystals without solvation and orange crystals with CH 2 Cl 2 solvate, although the reason was not clarified. 20,21 The origin of the dichromatic phenomena for 2a, 3a,b, and 5b was clarified by carefully analyzing their crystal structures, and the important structural parameters are summarized in Table 2. We found that intramolecular CH•••O hydrogen bonds between one of the methylene CH bonds in the dppe ligand and the EO (E = P, S) moieties were formed only in the red crystals of 2a and 5b and red-purple crystals of 3a,b.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although C-F bonds are stronger than C-H bonds, there is hitherto no clear correlation with any selectivity. 62 On a first glance, these reactivity pattern resemble those widely studied for fluoroaromatics. However, olefins allow for different reaction steps such as insertion or -Fand -H-elimination reactions.…”
Section: Account Synlettmentioning
confidence: 57%
“…Indeed, there is literature precedence for the generation of alkynyl complexes from vinylidene complexes in presence of a base. [55][56][57][58] Thus, a vacant coordination site can allow for a 1,2-uorine shi to yield a putative vinylidene complex [Rh(F)(]C]CHCF 3 )(PEt 3 ) 2 ] bearing a rhodium-bonded uorido ligand (Scheme 2). The latter complex would eliminate HF followed by an association of PEt 3 and form [Rh(C^CCF 3 )(PEt 3 ) 3 ] (6).…”
Section: Resultsmentioning
confidence: 99%